Artículo Científico. Haptic Stimulation Glove for Fine Motor Rehabilitation in Virtual Reality Environments - Borja Reinoso, Edgar Fabricio (2018)
This paper presents a fine motor rehabilitation system for upper limbs by using a virtual reality environment. For this purpose, a glove of stimulating bilateral haptic is built, which allows directly to determine the finger’s position through flexibility sensors. Also stimulate the medium and ulnar nerves of hand’s palm by using vibratory actuators in charge of feedback to contact with virtual surfaces. This system is based on bilateral communication between the virtual environment in the Unity 3D graphics engine and the haptic glove. It is respon-sible for analyzing the movements used by the patient and interact with the Ocu-lus Rift and Leap Motion for an increased immersion of the patient in the virtual rehabilitation environment. In addition, it generates vibrating feedback submitted to contact with virtual objects. The connection and transmission of data is done through wireless technologies in charge of creating a reliable and real time com-munication. The patient performs exercises based on fine motor rehabilitation which they are feedback with haptic glove and validated by algorithms based on Euclidean distance. The experimental results show the correct operation of the glove and the virtual environments oriented to virtual rehabilitation systems.